2022
DOI: 10.1038/s41598-022-08652-9
|View full text |Cite|
|
Sign up to set email alerts
|

Newly initiated carbon stock, organic soil accumulation patterns and main driving factors in the High Arctic Svalbard, Norway

Abstract: High latitude organic soils form a significant carbon storage and deposition of these soils is largely driven by climate. Svalbard, Norway, has experienced millennial-scale climate variations and in general organic soil processes have benefitted from warm and humid climate phases while cool late Holocene has been unfavourable. In addition to direct effect of cool climate, the advancing glaciers have restricted the vegetation growth, thus soil accumulation. Since the early 1900’s climate has been warming at unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…Generally, oxidative conditions reveal higher mass losses than smoldering conditions, which can be explained by more efficient combustion of the peat, whereas during oxygen-depleted smoldering, thermally induced condensation and aromatization reactions lead to the formation of coke residue. , NOR has, in general, higher TGA residues because of its higher mineral content. The sampling location of NOR is in the high Arctic areas covered by ice or tundra with short vegetation . Short and inefficient growing seasons lead to comparatively low peat formation, which is why deposition of mineral soil has a higher impact on the peat composition of NOR than for the other samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, oxidative conditions reveal higher mass losses than smoldering conditions, which can be explained by more efficient combustion of the peat, whereas during oxygen-depleted smoldering, thermally induced condensation and aromatization reactions lead to the formation of coke residue. , NOR has, in general, higher TGA residues because of its higher mineral content. The sampling location of NOR is in the high Arctic areas covered by ice or tundra with short vegetation . Short and inefficient growing seasons lead to comparatively low peat formation, which is why deposition of mineral soil has a higher impact on the peat composition of NOR than for the other samples.…”
Section: Resultsmentioning
confidence: 99%
“…The sampling location of NOR is in the high Arctic areas covered by ice or tundra with short vegetation. 60 Short and inefficient growing seasons lead to comparatively low peat formation, which is why deposition of mineral soil has a higher impact on the peat composition of NOR than for the other samples. Regardless of the applied measurement atmosphere, all peat samples reveal a similar mass loss step between 30 and 100 °C that can be attributed to the evaporation of residual water.…”
Section: Extractable Low-polar Species In Boreal Andmentioning
confidence: 99%
“…According to our data the lateral expansion development closely followed these climate patterns suggesting that the expansion dynamics in a bigger picture was controlled by climate. However, recent studies have shown a current drying trend in the peatlands of the North (Juselius et al., 2022; Zhang et al., 2020) that could have an adverse effect on the peatland expansion. It can also be hypothesized that during dry and warm climate periods, the peatland margins may have actually retreated instead of expanding due to peat oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The vegetation at the Svalbard study site (NOR) is characterized as herbaceous moss tundra. Notably, this peatland (NOR) is near a bird cliff which has a strong fertilizing effect, leading to an increased nitrogen content in the peat 57 . Naturally occurring wildfires have been reported for boreal peatlands in Finland and permafrost peatlands 89,90 , but not for Svalbard.…”
Section: Methodsmentioning
confidence: 99%
“…4a), NOR(−) shows a broad distribution of nitrogen-and sulfur-containing compounds between H/C = 0.6-2 and O/C = 0-0.5, while FIB(−) shows an ellipse-shaped distribution with moderate to high O/C ratios in the chemical space of phenol-like compounds, which were also observed as main products of Sphagnum moss decay in soil organic matter (SOM) analysis of a permafrost bog 56 . The high abundance of nitrogen-containing species in NOR is likely a result of the unique location of the peatland, close to a bird cliff ("Combustion conditions"), which increases the nitrogen content in the peat and consequently in the emitted PM (Supplementary Table 1) 57 . Both intersections also contain a small number of organophosphorus compounds (CHOP and CHN 1 OP), which have previously also been characterized by ESI(−) 21 T FT-ICR MS analysis of wildfire smoke, but with higher H/C ratios 41 .…”
Section: Effect Of Peat Origin On Organic Aerosol Compositionmentioning
confidence: 99%